The procedure of Anteroposterior Tooth Contact Adjustment (APTCA) in Orthodontic patients - Romanova Julia; Koval Svitlana (Journal of Dental Problems and Solutions - Peertechz Publications, 2017)
Orthodontic relapse is the major concern in both adolescent and adult orthodontic treatment. The causes of orthodontic relapse are reported to be of various origins. Functional diagnostic procedures allow to report the presence of disturbances in temporomandibular joint functioning, chewing muscle functioning and tooth contacts. The T-scan computerized occlusal analysis is aimed to diagnose the presence of tooth contacts that contribute to the overall imbalance in the occlusal pattern, the presence of force outliers which contribute to excessive teeth load and the timing characteristics of the functioning occlusion. The procedure of Anteroposterior tooth contact adjustment (APTCA) was worked out to analyze the presence of factors contributing to the anterior teeth movements after the completion of  orthodontic treatment and subsequently to diminish the risk of the orthodontic relapse caused by these tooth contacts.